Specific and Nonspecific Psychological Interventions for PTSD Symptoms: A Meta‐Analysis With Problem Complexity as a Moderator. Issue 7 (18th December 2013) - Gerger, Heike; Munder, Thomas; Barth, Jürgen
<x xml:space="preserve">Abstract</x> Context The necessity of specific intervention components for the successful treatment of patients with posttraumatic stress disorder is the subject of controversy. Objective To investigate the complexity of clinical problems as a moderator of relative effects between specific and nonspecific psychological interventions. Methods We included 18 randomized controlled trials, directly comparing specific and nonspecific psychological interventions. We conducted moderator analyses, including the complexity of clinical problems as predictor. Results Our results have confirmed the moderate superiority of specific over nonspecific psychological interventions; however, the superiority was small in studies with complex clinical problems and large in studies with noncomplex clinical problems. Conclusions For patients with complex clinical problems, our results suggest that particular nonspecific psychological interventions may be offered as an alternative to specific psychological interventions. In contrast, for patients with noncomplex clinical problems, specific psychological interventions are the best treatment option.